Perawatan Kateter Urine Dengan Chlorhexidine Gluconate 5% dalam Mencegah Infeksi Saluran Kemih - Muhamad Nor Mudhofar; Heru Purnomo; Mu'awanah Mu'awanah (Prodi Keperawatan Purwokerto, 2024)
Background: Urinary tract infections that occur in hospitals are mostly caused by the installation of indwelling urinary catheters. Indwelling urinary catheter care is one way to prevent catheter-related urinary tract infections. Objective: This study aims to determine the effect of indwelling urinary catheter treatment using 5% chlorhexidine gluconate on urinary tract infections in the Blora Hospital. Methods: This research uses a quasi-experimental posttest-only design. The sampling technique was purposive sampling, 12 subjects were recruited. The independent variable is indwelling urinary catheter care, and the dependent variable is urinary tract infection. Data were collected using colony counts and bacterial types on the fourth day. Data were analyzed by using the Mann Whitney test. Results: The results of the study showed that there was no difference in the incidence of urinary tract infections between patients in the treatment group who received indwelling urinary catheter treatment using chlorhexidine gluconate 5% and patients in the control group who received standard catheter treatment (p=0.138). Conclusion: Perineal care agents do not affect the incidence of catheter-related urinary tract infections. Further research should involve a larger number of respondents and consider respondent characteristics such as antibiotic use, diabetes mellitus, and urine production to obtain more accurate results.